Biochar particle size coupled with biofertilizer enhances soil carbon-nitrogen microbial pools and CO2 sequestration in lentil - Ahmad, Wiqar; Nepal, Jaya; Zou, Zhiyou; Munsif, Fazal; Khan, Aziz; Ahmad, Ijaz; Zaheer, Sajjad; Khan, Muhammad Shahid; Jadoon, Sultan Akbar; Tang, Danfeng (Frontiers in Environmental Science, 2023)
Biochar and biofertilizer have emerged as sustainable soil amendments to improve soil fertility and quality. However, it is necessary to determine how biochar's various particle sizes and biofertilizers affect soil microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), and CO2 sequestration. This research examined two rhizobia inoculum products-Biozote-N and Rhizogold-along with three biochar particle sizes (<2, 2-5, and 5-10 mm) under incubation intervals of 3, 6, and 10 days. The MBC (µg g -1 soil) and MBN (µg g -1 soil) increased significantly (p<0.05), however, a significant (p<0.05) decrease in the organic C and mineralizable C within the < 2mm biochar treatment was observed. With biochar size of 2 mm on day 3, the CO2 evolution was 25% lower, but it increased 4-19% from day 6-10 compared to the other biochar sizes and the biochar control. Sizes 2 and 2-5 mm were 43% lower in MBN, whereas 5-10 mm was 70% lower (ug g -1 OC). Biozote-N outperformed Rhizogold and nobiofertilizer on days 6 and 10, registering 6% and 20% higher MBC (g g -1 soil/OC), respectively. No biofertilizer increased CO2 production by 14% and 23% on days 3 and 6, respectively. On day 10, however, CO2 production inside Biozote and Rhizogold plots increased by 67% and 45% relative to the control, respectively. Biofertilizers enhanced MBN (ug g -1 OC) by 37%, with the contribution of Biozote-N being 18% more than that of Rhizogold. The Biozote-N and Rhizogold plots had a 13 and 28% increase in mineralizable N compared to the control. After the spring (lentil) crop, there was a 5-18% higher MBC (g g -1 soil), 6-17% higher MBC (g g -1 OC), 2-10% greater CO2 evolution, 23% higher MBN, and 77% higher mineralizable N than after the fall (maize) crop. The results demonstrated the usefulness of Biozote-N for enhanced MBC and MBN, as they decreased C mineralization at the small biochar size (2 mm) even after one year of their combined application to lentil crop, showing that biochar-Biozote-N were more successful at boosting soil organic fertility and C sequestration.